DETERMINAN HARGA SAHAM (Media Riset Akuntansi, 2022)
This study aimed to analyze the factors that affect the price of shares in mine companies listed on the Indonesia Stock Exchange in 2011-2015.The population of this study is mining industry for periods 2011-2015. Samples were selected by purposive sampling method using yearly data during 2011 to 2015 in order to obtain 40 samples. This study uses descriptive analysis method, the classical assumption (test for normality, heterocedasticity, multicollinearity test, and autocorrelation test ), a hypothesis testing ( t-test ( partial)), test the coefficient of determination ( R ²) and multiple regression analysis) by using theprogram SPSS 20 . The Hypothesis testing results show that the Current Ratio and Earning Per share partially positive effect on stock price. While Debt to Equity Ratio partially has no impact on stock price.